Evaluation of role of hyperbilirubinemia as a new diagnostic marker of complicated appendicitis - Bakshi, Sabyasachi (BMC Gastroenterol, 2021)
BACKGROUND: In appendicitis, elevated intra-luminal pressure and ischemic necrosis of mucosa causes tissue gangrene or perforation. This leads to cytotoxin facilitated progressive bacterial invasion or translocation into the hepatic parenchyma through portal system. This phenomenon interferes with the bilirubin excretion into the bile canaliculi. In the present study, establishment of a possible role of hyperbilirubinemia as a marker of gangrenous/perforated appendicitis has been studied. METHODS: After matching the inclusion and exclusion criteria, all cases of clinically diagnosed acute appendicitis were taken for this prospective, single center, observational study. Per-operative diagnosis was confirmed by histopathological examination. RESULTS: Out of 110 subjects of acute appendicitis 41 subjects (37.27%) had hyperbilirubinemia. Out of 35 subjects diagnosed as complicated appendicitis 32 subjects (91.42%) had raised total bilirubin levels, while the remaining 03 (8.58%) had normal levels. Among 75 subjects diagnosed as acute simple appendicitis 09 subjects (12%) had raised total bilirubin level, while the remaining 66 subjects (88%) had normal levels. It was Mixed Type of Hyperbilirubinemia in gangrenous/perforated appendicitis. The sensitivity of Total serum bilirubin in predicting complicated appendicitis was found 91.43% (76.942% to 98.196%), where as the specificity of this test was 88.00% (78.439% to 94.363%). positive predictive value and negative predictive value were 78.03% and 95.65% respectively. Positive likelihood ratio and negative likelihood ratio were found to be 7.619 and 0.097 respectively taking prevalence of complicated appendicitis be 31.80%. Receiver Operating Characteristic curve was obtained which shows optimal criterion at Total Bilirubin Level 1.06 mg/dl where sensitivity was 91.43% and specificity was 97.33% at 95% confidence interval with 31.8% disease prevalence. CONCLUSIONS: This is to conclude that Serum bilirubin level estimation, which is a simple, cheap and easily available laboratory test, can be added to the routine investigations in clinically suspected cases of acute appendicitis for early diagnosis of complications. Trial registration Registered with Clinical Trials Registry-India (ICMR-NIMS) with Registration number CTRI/2019/05/018879 Dated 01/05/2019. This was a prospective trial. Trial URL: http://ctri.nic.in/Clinicaltrials/pdf_generate.php?trialid=33113&EncHid=99780.32960&modid=1&compid=19%27,%2733113det%27.